A Content Analysis of Promotional Features in US Direct-Mail From Advertisements Across Tobacco Products From 2018 to 2020. Issue 10 (13th April 2022) - Silver, Nathan; Rahman, Basmah; Folger, Shanell; Bertrand, Adrian; Khatib, Bushraa; Gbenro, Macred; Schillo, Barbara
Abstract: Introduction: Direct-mail advertising is a crucial channel through which tobacco companies deliver price incentives that lower the barrier to tobacco use while promoting tobacco products via thematic appeals not legally permitted on other marketing channels. We examine the prevalence of price incentives and ad characteristics used in tobacco product advertisements (ads) mailed directly to US consumers. Aims and Methods: We analyzed the content of direct-mail tobacco ads ( N = 1047) in circulation between January 2018 and December 2020 as captured by Mintel Comperemedia Direct. These ads were coded for product type, manufacturer/brand type, model characteristics, price incentives, and themes known to appeal to vulnerable subgroups. Results: Ads across all tobacco products included price incentives (96%) and contained themes that appealed to rural white (40%) and black audiences (15%). Themes known to appeal to youth and young adults were present in 40% of ads across all products, including 78% of ads promoting electronic nicotine delivery systems (ENDS). Moreover, the ENDS ads featuring youth appealing themes (51%), also featured young models. Discussion: Expanding on previous research which focused on combustible and smokeless tobacco products, this analysis examines direct-mail ads across the full range of tobacco products. Our findings highlight the need for regulations to address (1) the high prevalence of price incentives that undermine the effectiveness of excise taxes on tobacco use, and (2) ad themes and characteristics that appeal to groups vulnerable to tobacco use, both of which have the potential to further exacerbate tobacco-related health disparities. Implications: This study reinforces the importance of examining direct-mail as the dominant medium for tobacco advertising, particularly by including coupons and discount codes that reduce product price and thus circumventing the effect of tobacco-related tax legislation. Direct-mail encourages continued product loyalty and use and engages new consumers using price incentives and advertising strategies likely to appeal to price-sensitive consumers and other vulnerable populations. Substantial use of youth-appealing elements in ENDS ads contradicts the tobacco industry's mandate to not appeal to youth, warranting highlighting the gaps in current regulations that allows them to continue appealing to this population.